Photometry of Particles Ejected From Active Asteroid (101955) Bennu. Issue 9 (26th August 2020) - Hergenrother, C. W.; Maleszewski, C.; Li, J.‐Y.; Pajola, M.; Chesley, S. R.; French, A. S.; Davis, A. B.; Pelgrift, J. Y.; Leonard, J. M.; Shelly, F.; Liounis, A. J.; Becker, K.; et al.
Abstract: Near‐Earth asteroid (101955) Bennu is an active asteroid experiencing mass loss in the form of ejection events emitting up to hundreds of millimeter‐ to centimeter‐scale particles. The close proximity of the Origins, Spectral Interpretations, Resource Identification, and Security–Regolith Explorer spacecraft enabled monitoring of particles for a 10‐month period encompassing Bennu's perihelion and aphelion. We found 18 multiparticle ejection events, with masses ranging from near zero to hundreds of grams (or thousands with uncertainties) and translational kinetic energies ranging from near zero to tens of millijoules (or hundreds with uncertainties). We estimate that Bennu ejects ~10 4  g per orbit. The largest event took place on 6 January 2019 and consisted of ~200 particles. The observed mass and translational kinetic energy of the event were between 459 and 528 g and 62 and 77 mJ, respectively. Hundreds of particles not associated with the multiparticle ejections were also observed. Photometry of the best‐observed particles, measured at phase angles between ~70° and 120°, was used to derive a linear phase coefficient of 0.013 ± 0.005 magnitudes per degree of phase angle. Ground‐based data back to 1999 show no evidence of past activity for Bennu; however, the currently observed activity is orders of magnitude lower than observed at other active asteroids and too low be observed remotely. There appears to be a gentle decrease in activity with distance from the Sun, suggestive of ejection processes such as meteoroid impacts and thermal fracturing, although observational bias may be a factor. Plain Language Summary: We measured the brightness of pebble‐sized particles in the vicinity of near‐Earth asteroid Bennu to better understand their physical characteristics and the events that launched them from Bennu's surface. Our measurements spanned 10 months, encompassing Bennu's closest and farthest distances from the Sun, so that we could assess how the level of ejection activity changes with solar distance. We observed 18 multiparticle ejection events containing anywhere from a few to 200+ particles. Individual particles ranged from millimeters to centimeters in diameter. The energy of the events and a possible decrease in activity with larger distances from the Sun suggest that meteoroid impacts, fracturing of surface boulders due to solar heating, or both may be responsible for ejecting the particles. We estimate that Bennu releases ~10, 000 g of material over one orbit or 1.2 years. Although mass loss has been remotely observed for other asteroids, the comparatively low level of particle ejection activity at Bennu was only observable thanks to the close proximity of the Origins, Spectral Interpretations, Resource Identification, and Security–Regolith Explorer spacecraft. Key Points: Asteroid (101955) Bennu is active from perihelion through aphelion with a possible decrease in activity further from the Sun Bennu's activity is less than that detected by telescope for other active asteroids and is only observable up close The particles' shallow phase functions resemble those of similarly sized individual rocks rather than those of ensemble asteroid surfaces